Snowboarders: Bodies out of control and in conflict - Humphreys, D. E. (Sporting Traditions, 1996)
This article discusses snowboarding and snowboarders` relationships with skiing and skiers. The latter `represent` local authorities `on site`, that is, on the mountain. Skiing`s long history and acceptance as a legitimate` pastime and sport endow skiers with a form of authority. This article contends that snowboarders contravene skiers` definitions of what constitutes `acceptable bodies`. This article also attempts to situate these relationships within changes in late capitalism and its profound impact on society over the last fifty years.